Optimization of the Utilization of Registered Non-Hazardous Waste (Fly Ash and Bottom Ash from Coal-Fired Power Plants) Based on Their Physical and Chemical Properties - Ofi Shofiyah; Suyud Warno Utomo; Haruki Agustina (Green Publisher Indonesia, 2025)
This study examines the influence of affiliate content type and source credibility on perceived trust and purchase intention within TikTok Shop, specifically focusing on air freshener products. The research highlights the critical role of energy supply in development, emphasizing the increasing demand for energy, particularly from coal-fired power plants in Indonesia. It discusses the generation and management of coal ash waste, including Fly Ash and Bottom Ash, and the recent policy changes that categorize these as non-hazardous waste. The study outlines sustainable strategies for utilizing this waste, addressing both environmental concerns and economic opportunities. Through a quantitative approach, data were collected from coal-fired power plants, revealing insights into waste management practices and the potential for enhancing the sustainability of FABA waste utilization. The findings aim to contribute to the body of knowledge on waste management and provide practical benefits for industries involved in energy production and waste utilization.